Optimization of the Performance of the Intelligence Unit through Early Detection to Prevent Conflicts between Pencak Silat Schools in the Jurisdiction of the Karanganyar Police - Hari Cahyo Purnomo (Akademi Kepolisian Republik Indonesia, 2023)
This research is motivated by the case of the Pencak Silat Organization in the Karanganyar Regency Region. The Pencak Silat Oganization case is not a new case in the Karanganyar Region. The rise of this case has received special attention from the Karanganyar Police because it not only has an impact on material losses but has resulted in fatalities. Therefore, in order to create a conducive Kamtibmas situation, it is necessary to prevent conflicts between Pencak Silat Organization. Prevention will be carried out through optimizing the performance of the intelligence unit through early detection. The theory used to analyze is the theory of function management and conflict management. The concept used as a theoretical basis, namely the concept of optimization and intelligence investigation. The approach used in this study is a qualitative approach with descriptive analysis to process the data obtained in the field. Sources of information obtained from primary and secondary data sources. The data collection techniques used were interviews, observation and document studies. Based on the results of research conducted by the Karanganyar Police, the performance of the Satintelkam Police is considered to be not optimal with the occurrence of pencak silat organization conflicts in the Karanganyar Regency area. As well as, there is still a lack of product manufacture and filing from the Karanganyar Police's Satintelkam. In preventing and resolving conflicts that have been carried out, they are still not effective so that new, better innovations are needed so that the conflicts in pencak silat organization can be resolved. This study provides several suggestions that can be made by Satintelkam, including preparing intelligence administration in a systematic manner and the need to improve coordination between agencies related to the National Police both within and outside the Karanganyar Regency area.